METHOD OF EVALUATION OF THE EFFICIENCY OF TELECOMMUNICATION NETWORK MANAGEMENT SYSTEM - Eduard N. Bovda; Oksana G. Gavriluk; Оleksandr M. Guk (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article analyzes existing approaches and methods for assessing the efficiency of a telecommunication network and its management system. The concept of efficiency, classification and existing approaches to its evaluation are considered. A number of indicators of telecommunication network efficiency characterizing the target, technical (technological), economic efficiency of the telecommunication network are given. The indicators of efficiency of the telecommunication network management system are considered. The method of estimation of efficiency of routing methods as a subsystem of routing management of a telecommunication network management system, which consists of seven stages, is presented. Indicators of the effectiveness of routing methods are considered as three groups of indicators, which are divided into global, local and operational financial. The efficiency of routing methods (by parameters of productivity, packet delay time) is given when changing the topology and different routing methods for fixed input load and network dimension. It is shown that the efficiency of the control system is determined by the efficiency of the telecommunication network.